Antioxidants and Antityrosinase Activity of Ethanolic Basil Leaves Extract (Ocimum americanum L.) and Eygenol - Dio Damara Handoyo; Ermi Girsang; Ali Napiah Nasution; I Nyoman Ehrich Lister (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Harm effect from UV light, both UV-A and UV-B is contributing as a disease trigger and has an impact on human health. To investigate the bioactive compound, antioxidant, and the potential of basil leaves as antiaging sources particularly as the tyrosinase inhibitor. This study used phytochemical screening for the bioactive compound, DPPH scavenging activity for antioxidant assay, and tyrosinase inhibition activity for the antiaging property. The phytochemical screening shows that the basil leaves extract has flavonoid, saponin, phenol, steroid, and alkaloid. The basil leaves extract has lower antioxidant activity (20.55 ± 0.04 μg/mL) compared with eugenol (2.44 ± 0.26 μg/mL) through DPPH scavenging activity. The basil leaves extract (35.59 ± 0.83 μg/mL) has lower antiaging activity particularly as antityrosinase activity compared with eugenol (10.87 ± 0.41 μg/mL). Our findings suggest that basil leaves can be used as an antioxidant and antiaging source, particularly as a tyrosinase inhibitor.